Pemanfaatan Media Sosial Tiktok Sebagai Media Komunikasi Pemasaran untuk Meningkatkan Nilai Jual Bagi Usaha Mikro, Kecil dan Menengah di Pasar Tanah Abang - Indrawan, Robby; Marbu Linko, Bagas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Marketing is the most important aspect in business. There are many ways to market products or services, one of which is social media. Social media is an online medium where users can easily participate, share and create content including blogs, social networks, wikis, forums and virtual worlds. Blogs, social networks and wikis are the most popular forms of social media used by people, Tiktok is an application that provides unique and interesting special effects as a marketing medium. The aim of this study is to analyze the use of TikTok social media as a marketing medium to increase the selling value of UMKM at Tanah Abang Market. This study uses a qualitative approach with a case study method collected through observation, interviews and literature study. According to the findings of this study, Tiktok is an effective marketing medium for increasing sales.